2003
DOI: 10.1001/jama.289.8.1001
|View full text |Cite
|
Sign up to set email alerts
|

Patients' and Physicians' Attitudes Regarding the Disclosure of Medical Errors

Abstract: Context Despite the best efforts of health care practitioners, medical errors are inevitable. Disclosure of errors to patients is desired by patients and recommended by ethicists and professional organizations, but little is known about how patients and physicians think medical errors should be discussed. Objective To determine patients' and physicians' attitudes about error disclosure. Design, Setting, and Participants Thirteen focus groups were organized, including 6 groups of adult patients, 4 groups of aca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
638
2
37

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 817 publications
(714 citation statements)
references
References 53 publications
21
638
2
37
Order By: Relevance
“…Gallagher and colleagues [13] found patients desire and expect to be informed promptly about a medical error; to be given information about what occurred, why and how it occurred, how their health will be affected, and what steps will be taken to prevent future harm; and to receive an apology that signals a sense of regret and a desire to do better going forward. Indeed, they found ''[m]any patients said they would be less upset if the physician disclosed the error honestly and compassionately and apologized… [and]…that explanations of the error that were incomplete or evasive would increase their distress'' [13]. Patients also prefer that such communication occur without a need for prompting on their part [13].…”
Section: Apologies and Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gallagher and colleagues [13] found patients desire and expect to be informed promptly about a medical error; to be given information about what occurred, why and how it occurred, how their health will be affected, and what steps will be taken to prevent future harm; and to receive an apology that signals a sense of regret and a desire to do better going forward. Indeed, they found ''[m]any patients said they would be less upset if the physician disclosed the error honestly and compassionately and apologized… [and]…that explanations of the error that were incomplete or evasive would increase their distress'' [13]. Patients also prefer that such communication occur without a need for prompting on their part [13].…”
Section: Apologies and Patientsmentioning
confidence: 99%
“…Indeed, they found ''[m]any patients said they would be less upset if the physician disclosed the error honestly and compassionately and apologized… [and]…that explanations of the error that were incomplete or evasive would increase their distress'' [13]. Patients also prefer that such communication occur without a need for prompting on their part [13].…”
Section: Apologies and Patientsmentioning
confidence: 99%
“…After being involved in an error, many nurses neither received the support they needed nor knew where to find such support (Scott et al, 2009;Waterman et al, 2007). Most health care institutions did not have 18 adequate support systems in place to assist staff with coping and adapting after an error (Gallagher et al, 2003;Schwappach & Boluarte, 2008).…”
mentioning
confidence: 99%
“…Medical malpractice premiums have skyrocketed in recent years, most significantly in specialties such as obstetrics-gynecology and neurosurgery, and as a result many physicians fear that every patient is a potential litigant [2]. Two national surveys designed to assess attitudes toward disclosure revealed that fear of litigation was the primary reason for both physicians' and hospitals' reluctance to disclose errors and unanticipated outcomes [3,4].…”
Section: The Risks Of Saying "I'm Sorry"mentioning
confidence: 99%